Tantangan Multikulturalisme di Indonesesia dalam Disintegrasi Umat Beragama - Rachmadyastuti, Amanda; Nandani, Shinta Ayu Sri; Saputra, Rio; Husna, Yasmin Syarifah Al-; Rahma, Fatimah Nur (MASALIQ, 2022)
Indonesia is a country that is rich in various tribes, beliefs, races, cultures, and customs. This diversity is an important asset to be maintained with tolerance between individuals. Tolerance must also be applied in religious life because religion is the life-breath of the Indonesian people, stated in the first precepts. The existence of tolerance between religious communities in the implementation of holidays and other significant days will reduce the occurrence of social disintegration in society. This study aims to determine the various factors that cause intolerance, one of Indonesia's multicultural challenges, and their solutions. Through a qualitative research method of literature study, this research compares various events based on relevant sources in the main topic of religious tolerance. The research results that found many case studies showed that many factors triggered social conflicts with religious nuances, including cultural, political, and economic factors. In addition, religious factors can also be one of the triggers for conflict between the wider community, leading to social disintegration on the broader community.